2-furfural content in beer - Kiriienko, Serhii; Mukoid, Roman (My University, 2024)
During the production of beer, there are defects associated with raw materials, incorrect management of the technological process, which subsequently leads to violations of the biological, physico-chemical and, in fact, organoleptic properties of beer. Therefore, research, detection and elimination of defects in brewing, which are formed as a result of oxidation and aging of beer, are relevant.

При виробництві пива мають місце дефекти сировини, неправильне ведення технологічного процесу, що згодом призводить до порушення біологічних, фізико-хімічних і, власне, органолептичних властивостей пива. Тому дослідження, виявлення та усунення дефектів пивоваріння, які утворюються внаслідок окислення та старіння пива, є актуальними.
Keywords: кафедра біотехнології продуктів бродіння і виноробства; furfural; beer; beer oxidation; spectrophotometry; фурфурол; пиво; окислення пива; спектрофотометрія